And this is what we sing – what do we sing? Exploring the football fan songs of the Northern Irish 'Green and White Army'. (December 2021) - Bell, John; Bell, Paul
This paper draws upon digital recordings of Northern Ireland football fans singing in the stadium during all 10 qualifying matches for the 2016 UEFA European Football Championship. Supplemented by participant observation and interview data with 21 supporters themselves, the paper challenges assertions within the literature which focus upon the predominance of sectarian singing amongst a section of Northern Ireland football supporters. Although vocal manifestations of football fandom may initially appear to be randomly driven by irrational emotions, on the contrary, there is an underlying structure and sequence to fandom in the stadium in which certain factors promote collective singing at particular times. The paper identifies four key themes in particular: the timing in a match; whether or not a goal has been scored; if there is a lull or a break in play; and the use of musical instruments to encourage the wider collective to sing. We argue that it is important to understand the process by which collective singing occurs in the football stadium rather than fixating upon the alleged racist or sectarian psychopathology of the individuals involved. Such knowledge may assist in supporting those fan organisations that seek to challenge discriminatory behaviour in the stadium, particularly in the current context of the European (UEFA) and World football governing bodies (FIFA) punishing fans collectively, regardless of whether or not the majority in the stadium are opposed to what is being sung in their name.